Consumers’ Preference toward Islamic Banking (Case Study in Bank Muamalat Indonesia and Bank BNI Syariah) - Delta Khoirunissa (Jurnal Iqtisad, 2003)
Information on consumers’ characteristics and behaviors is very important as one of strategic efforts to develop Islamic banking. How is a consumer’s characteristic and be-havior? What factors are motivating this consumer to choose Islamic banking?This research aims at providing empirical evidence on factors motivating consumers to save in Islamic banking, and proving the relationship between economic and religious preferences in motivating consumers to save in Islamic banking. The analysis of variance and chi-square are respectively used in this research.The results evidence that consumers’ decision to save in Islamic banking are influ-enced by economic factors, such as receiving economic benefits, quick services, online fa-cilities, and easy reachable locations, as well as healthy financial systems. Likewise, con-sumers’ decision to save in Islamic banking are influenced by religious factors, such as not in opposition to Islamic teachings/obeying religious orders, lessening economic imbal-ances in society, having good understanding on Islamic principles, and getting informa-tion/knowledge concerning Islamic banking, as well as living in a religious supporting en-vironment. Moreover, external factors such as motivation from parents, brothers or sisters, friends, and bank employees, as well as Moslem scholars are also influencing consumers’ decision to save in Islamic banking.The existence of the relationship between economic and religious preferences proves that, in making decision, consumers wish to attain two satisfaction levels, i.e. satisfaction in the world and in the hereafter.Keywords: economic preferences, religious preference, and Islamic banking.